1994
DOI: 10.1073/pnas.91.19.9165
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of microtubules in the link between cell volume and pH of acidic cellular compartments in rat and human hepatocytes.

Abstract: Cell swelling is shown to induce an increase in acridine orange fluorescence intensity, an effect pointing to the alkalinization of acidic vesicles. Since autophagic hepatic proteolysis is accomplished by pH-sensitive proteinases within acidic lysosomes, this effect may contribute to the well-known inhibitory effect of cell swelling on proteolysis. In the present study, the role ofmicrotubules in volume-dependent alterations of pH in acidic vesicles of rat and human hepatocytes was studied. Colcemid and colchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 27 publications
2
44
0
Order By: Relevance
“…As reported earlier in studies on FITC-dextran or acridine orange-loaded hepatocytes (27,(43)(44)(45), hypo-osmotic exposure of rat hepatocytes leads to an alkalinization of endocytotic vesicles, whereas hyperosmotic hepatocyte shrinkage induced acidification. The functional significance, however, remained unknown.…”
Section: Figure 3 Hyperosmotic Ros Generation Is Abolished After P47mentioning
confidence: 65%
“…As reported earlier in studies on FITC-dextran or acridine orange-loaded hepatocytes (27,(43)(44)(45), hypo-osmotic exposure of rat hepatocytes leads to an alkalinization of endocytotic vesicles, whereas hyperosmotic hepatocyte shrinkage induced acidification. The functional significance, however, remained unknown.…”
Section: Figure 3 Hyperosmotic Ros Generation Is Abolished After P47mentioning
confidence: 65%
“…A decrease of extracellular osmolarity leads to osmotic cell swelling, which modifies a variety of cellular functions, such as transport, metabolism, cell proliferation, and cell death (for a review, see reference 27). Most notably, it is well established that cell swelling results in alkalinization whereas cell shrinkage results in acidification of endosomal pH (10)(11)(12)(13)(14)(15)(42)(43)(44). Previous investigations have shown that, due to inhibition of the fusion of the phagosome and lysosome, the phagosome of L. pneumophila does not become acidified (25,26,38) and therefore enables the intracellular multiplication of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular Ca 2 has been shown to increase upon cell swelling (Hoffmann & Simonsen, 1989;Baquet et al, 1991b;contrast Schreiber et al, 1996, who found no change), but this cannot explain the antiproteolytic effect of cell swelling because an increase in Ca 2 results in activation rather than in inhibition of macroautophagy (Caro, 1989;Gordon et al, 1993). Recent work by Häussinger and colleagues (Schreiber & Häussinger, 1995;Schreiber et al, 1996) with fluorescein isothiocyanate (FITC)-dextran indicates that cell swelling causes alkalinization of an early endocytic compartment rather than alkalinization of the lysosomes, as was originally thought (Busch et al, 1994). The latter finding is in line with recent data of Luiken et al (1996): in order to monitor changes in lysosomal pH in hepatocytes, we used the pH-dependent conversion of lysylalanyl-4-methoxy-2-naphthylamide to lysylalanine and fluorescent 4-methoxy-2-naphthylamine by the lysosomal enzyme dipeptidylpeptidase II, and also failed to observe changes in lysosomal pH after hypo-osmotic swelling of the cells.…”
Section: Control By Amino Acids and Hormonesmentioning
confidence: 98%